Performance Evaluation of IoT Communication Protocols (LoRa, Wi-Fi and Zigbee) for Smart Environment - Fahmi, Arif Fahmi; Indra Kurniawan; Junaedi Adi Prasetyo (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
The Internet of Things (IoT) constitutes a core component in the development of Smart Environment systems for real-time environmental monitoring. Selecting an appropriate communication protocol remains a major challenge, particularly in semi-rural areas characterized by limited network infrastructure and heterogeneous geographical conditions. This study aims to evaluate and compare the performance of three IoT communication protocols, namely LoRa, WiFi (ESP32), and Zigbee (XBee), through real-field prototype-based testing conducted in the semi-rural region of Banyuwangi. The evaluated parameters include communication range, transmission latency, and packet delivery ratio (PDR). The experiments were performed by periodically transmitting data packets under multiple distance scenarios. The results indicate that LoRa achieves the longest communication range of approximately ±1750 meters with an average latency of 2.1 seconds, WiFi exhibits the lowest latency of about 0.2 seconds with an effective range of ±200 meters, while Zigbee demonstrates stable transmission performance with a PDR of 100% up to a distance of ±600 meters. The main contribution of this study lies in providing empirical performance data obtained from real-field experiments in a semi-rural Indonesian environment, which can serve as a reference for selecting appropriate IoT communication protocols for Smart Environment implementations.